Forms, Development and The Application of Music Media in The Kindergartens: A Comparative Study of Two Kindergartens - Sumaryanto F., Totok; Utomo, Udi (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2015)
This study was aimed at investigating the form of music media employed in the teaching and learning process (TLP) in the kindergartens, and the teachers’ effort to develop and apply music media in the TLP. The researchers used a qualitative approach. The research was conducted in TK Hj. Isriati Baiturahman and TK Negeri Pembina Semarang. The subjects of the study were principals, teachers, staffs and students. In collecting the data, the researchers used three different techniques: interview, observation and documentation. Then, the researchers used data reduction, categorization and data interpretation to analyse the data. The result shows that the teachers in both schools have utilized varied music media in the TLP. In TK Hj. Isriati, the teachers used music media in the form of music composition and electronic equipment; and the new music instruments were used by the teachers in extracurricular activities. Meanwhile, the teachers in TK Negeri Pembina utilized music media including music composition, music instruments and electronic equipment. The development of music media by the teachers was done by modifying lyrics, composing simple songs, utilizing rhitmical music instruments and employing electronic equipment in the TLP.